Reproductive characteristics and life‐history relationships of starry smooth‐hound Mustelus asterias in British waters. Issue 6 (December 2015) - McCully Phillips, S. R.; Ellis, J. R.
Abstract : The reproductive biology and other life‐history parameters were investigated for Mustelus asterias in British waters, with specimens caught from both commercial fisheries and research‐vessel surveys. In total, 504 specimens [238 males, 24–99 cm total length ( L T ) and 266 females, 28–124 cm L T ] were examined, with further information collected from 238 uterine pups. The lengths at 50% maturity were estimated as 70·4 and 81·9 cm L T for males and females, respectively. Ovarian fecundity ranged from one to 28, and uterine fecundity from four to 20. The number, mass and L T of pups were positively correlated with maternal L T . Full‐term pups ranged from 205 to 329 mm L T, and the smallest free‐living fish caught was 24 cm L T . Parturition occurred in February in the western English Channel and during June to July in the eastern English Channel and southern North Sea, indicating either protracted spawning or asynchronous parturition for the stock as a whole. The reproductive cycle is thought to extend beyond 1 year. Developmental abnormalities observed included atresia in oocytes, uterine eggs that failed to develop, a partly developed pup and an abnormal male with a single aberrant clasper. Data relating to conversion factors, oocyte numbers and diameter and gonado‐somatic and hepato‐somatic indices are presented, and the seasonality of the reproductive cycle is discussed.